Mean drop size correlations and population balance models for liquid-liquid dispersion - Zainal Abidin, M.I.I.; Abdul Raman, Abdul Aziz; Mohamad Nor, Mohamad Iskandr (John Wiley & Sons, 2015)
Reliable models are required for accurate estimation of drop sizes which govern the interfacial area and rate of mass transfer in a system where various correlations and models have been improved for better accuracy and wider application breath. In this article, relevant semiempirical equations and population balance equation (PBE) models are reviewed. Semiempirical correlations are highly system dependent and limited to prediction of steady-state drop size while PBE models could estimate transient drop size with considerations of inhomogeineity and flow spatial variation during drop size evolution. With appropriate model parameters determination, different PBE models can be used to reproduce experimental data for a similar system.